Desenvolvimento e aplicação de um sistema de diagnóstico Fuzzy baseado em modelos para reatores UASB tratando esgoto sanitário - Borges, Raquel Machado (2005)
This work deals with the development and the application of a model based fuzzy diagnostic system to UASB reactors treating domestic wastewater. The diagnostic system is composed by three integrated modules. The first one estimates the influent chemical oxygen demand concentration. The second module estimates the biogas production in the reactor. The third one uses all information obtained from modules 1 and 2 to provide diagnoses of the plant operational status. The diagnostic system and the models were developed based on fuzzy logic. The diagnostic system was applied to two other UASB reactors treating sewage for validation.